SIGLO 20 a century of style and design in the Philippines - Lico, Gerard (Manila National Commission for Culture and the Arts, 2016)
This compendium presents some diverse examples that capture the ingenuity of unsung heroes - designers and innovators - and their products that changed lives of the Filipino across decades of the 20th century, that will invoke some form of nostalgia and remembrance of the past.
Introduction : one hundred years of change -- 1900-1919 : Building the American tropical empire and the benevolent creation -- 1920-1929 : Art Deco decadence and the jazz age -- 1930-1939 : Peacetime and streamlining -- 1940-1949 : War, destruction and the nostalgia for nation -- 1950-1959 : Postcolonial modernity, space age and the new look -- 1960-1969 : Cult of the youth and social decadence -- 1970-1979 : The new society and the neurosis for identity -- 1980-1989 : The Edsa revolution and the new design revolution -- 1990-1999 : Post-modernity, sustainable design and the "anything goes style" -- Epilogue : At century's end
Keywords: Architecture -- History. -- Philippines; Decorative arts -- History -- 20th century. -- Philippines; Design -- History -- 20th century. -- Philippines